Sistem Informasi Manajemen Keuangan Rumah Tangga Berbasis Object Oriented Programing (Java Desktop App) - Subiksa, Gde Brahupadhya; Peling, Ida Bagus Adisimakrisna; Ariawan, Made Pasek Agus; Prayudha, Putu Astya (Program Studi Teknik Informatika Universitas Pamulang, 2025)
The application of information technology in household financial management has provided individuals with the convenience of being more disciplined in recording income and expenses. This study aims to develop a desktop-based household financial management application using Object-Oriented Programming (OOP). The application is designed to facilitate transaction recording, financial goal planning, and financial analysis, which can help users make more informed financial decisions. The development method employed is Agile Development, following sprint stages including requirements analysis, design, development, testing, and deployment. System testing was conducted using the black-box testing method to ensure that the application functions as expected. The testing results showed a high level of success, with an overall success rate of 98% for the core features of the application, such as transaction recording, financial goal planning, and financial analysis. There was a minor issue identified with the category management feature, with an error rate of approximately 2%, which will be addressed in the next development phase. The application was also tested across various usage scenarios and demonstrated optimal performance in managing household financial data without significant issues. In conclusion, the application successfully achieves its goal of providing a practical and effective solution for household financial management. With a success rate of 98% for its main features, the application is ready for real-life implementation. Recommendations for future development include enhancing integration with external financial services and developing a mobile version to expand user reach.